2002
DOI: 10.1159/000065214
|View full text |Cite
|
Sign up to set email alerts
|

Hemostasis and Fibrinolysis Factors in First-Degree Relatives of Patients with Type 2 Diabetes without Hypertension

Abstract: First-degree relatives of type 2 diabetic patients with or without a family history of hypertension are at increased risk for cardiovascular diseases. The aim of this study was to verify some possible hemostatic alterations in first-degree relatives of type 2 diabetic, normotensive and hypertensive patients. In 78 non-diabetic, normotensive first-degree relatives of type 2 diabetic patients (47 without a family history of hypertension and 31 with a family history of hypertension) and in 36 normoglycemic, normo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Increased plasma D-dimer levels not only can predict a range of adverse health outcomes in the general population ( 11 , 34 ) but also can partly account for metabolic diseases and vascular complications with a background of insulin resistance. When compared to the healthy controls, the level of plasma D-dimer was obviously elevated in the first-degree relatives of T2D ( 35 ), prediabetes ( 18 ), gestational hypertension ( 36 ), polycystic ovary syndrome ( 37 ), and metabolic syndrome ( 38 ), let alone in overt T2D. Moreover, plasma D-dimer was observed to be independently associated with inflammatory cytokines ( 39 ), oxidized LDL ( 40 ), poor glycemic control (hyperglycemia, glycemic variability, and hypoglycemia) ( 41 43 ), diabetic retinopathy and nephropathy ( 14 , 15 ), and CVD ( 17 ) in patients with T2D.…”
Section: Discussionmentioning
confidence: 97%
“…Increased plasma D-dimer levels not only can predict a range of adverse health outcomes in the general population ( 11 , 34 ) but also can partly account for metabolic diseases and vascular complications with a background of insulin resistance. When compared to the healthy controls, the level of plasma D-dimer was obviously elevated in the first-degree relatives of T2D ( 35 ), prediabetes ( 18 ), gestational hypertension ( 36 ), polycystic ovary syndrome ( 37 ), and metabolic syndrome ( 38 ), let alone in overt T2D. Moreover, plasma D-dimer was observed to be independently associated with inflammatory cytokines ( 39 ), oxidized LDL ( 40 ), poor glycemic control (hyperglycemia, glycemic variability, and hypoglycemia) ( 41 43 ), diabetic retinopathy and nephropathy ( 14 , 15 ), and CVD ( 17 ) in patients with T2D.…”
Section: Discussionmentioning
confidence: 97%
“…D-dimers are small protein fragments produced during fibrinolysis and are well-established markers of venous thrombosis formation in the general population [ 42 ]. Previous studies indicated that increased D-dimer concentration was found in individuals with prediabetes [ 43 ], type 2 diabetes patients [ 42 ], or even first-degree relatives of type 2 diabetes patients [ 44 ]. Cheng et al [ 45 ] showed that patients with type 2 diabetes who have high plasma concentrations of D-dimer are at an increased risk of cardiovascular disease events, even after adjusting for cardiovascular risk factors and treatments.…”
Section: Discussionmentioning
confidence: 99%
“…However, alternative explanations are indispensable because the independent association between a family history of diabetes and increased IMT persisted after adjusting for HbA1c, total cholesterol, and triglyceride levels. This independent association could be related to endothelial dysfunction [ 30 ], impaired fibrinolysis [ 31 ], as yet unidentified genetic factors, inflammatory processes [ 14 ], or interactions or mediating effects not considered in our analysis. A previous study suggested that elevated fasting and postprandial glucose concentrations in the offspring of patients with type 2 diabetes could lead to the loss of endothelial function, resulting in increased IMT [ 15 ].…”
Section: Discussionmentioning
confidence: 99%